2022
DOI: 10.3389/fphar.2022.870699
|View full text |Cite
|
Sign up to set email alerts
|

Liquiritin Attenuates Pathological Cardiac Hypertrophy by Activating the PKA/LKB1/AMPK Pathway

Abstract: Background: Liquiritin (LQ) is one of the main flavonoids extracted from the roots of Glycyrrhiza spp., which are widely used in traditional Chinese medicine. Studies in both cellular and animal disease models have shown that LQ attenuates or prevents oxidative stress, inflammation, and apoptosis. However, the potential therapeutic effects of LQ on pressure overload-induced cardiac hypertrophy have not been so far explored. Therefore, we investigated the cardioprotective role of LQ and its underlying mechanism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 58 publications
0
6
0
Order By: Relevance
“…20 Recent studies have reported that LQ exerts cardioprotective effects by attenuating oxidative stress injury, reducing the expression of inflammatory factors, inhibiting cell apoptosis, restoring cardiac functional parameters and maintaining structural integrity. [21][22][23] In addition, many traditional Chinese medicine formula containing LQ have been used to treat cardiovascular diseases, especially ischemic heart disease, such as Zhigancao Decoction, 24 Xuefu Zhuyu Decoction, 25 Yangxin Dingji Capsule, 26 etc. However, the effect of LQ on MI-induced damage remains poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…20 Recent studies have reported that LQ exerts cardioprotective effects by attenuating oxidative stress injury, reducing the expression of inflammatory factors, inhibiting cell apoptosis, restoring cardiac functional parameters and maintaining structural integrity. [21][22][23] In addition, many traditional Chinese medicine formula containing LQ have been used to treat cardiovascular diseases, especially ischemic heart disease, such as Zhigancao Decoction, 24 Xuefu Zhuyu Decoction, 25 Yangxin Dingji Capsule, 26 etc. However, the effect of LQ on MI-induced damage remains poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…AMPKα2 is the primary subunit of AMPK in the myocardium and ablation of AMPKα2 leads to pathological cardiac remodeling and dysfunction [21] . Recently, Tang’s group has shown that activation of the cAMP/PKA/LKB1/AMPKα2 signaling pathway underlies the protective effects of Liquiritin against pathological cardiac hypertrophy [22] . Thus, in addition to AMPKα1,we wonder whether Metrnl OE affected AMPKα2 signaling in cardiomyocytes.…”
Section: Resultsmentioning
confidence: 99%
“…It is likely that the LKB1/AMPK/ULK1/autophagy axis might partially contribute to the beneficial effects of Metrnl on diabetic cardiac injury. The AMPK/mammalian phosphorylation target of rapamycin (mTOR)signaling pathway is an important regulator of DCM [27] , and LKB1 induces AMPKα phosphorylation at Thr 172 within its catalytic subunit, leading to AMPK-mediated inhibition of mTORC1 and subsequent activation of autophagy [22] , [28] , [29] . Thus, we next sought to examine whether mTORC1 was involved in the induction of autophagy mediated by Metrnl.…”
Section: Resultsmentioning
confidence: 99%
“…Liquiritin could also decrease heart size, cardiac cross-sectional area (CSA), and heart weight/body weight (HW/BW), and inhibited the messenger RNA (mRNA) expression of A type natriuretic peptide (ANP), B type natriuretic peptide (BNP), and β-myosin heavy chain (β-MHC). In vitro, liquiritin inhibited Ang II-induced hypertrophy in neonatal rat cardiomyocytes (NRCMs) via activating cyclic adenosine monophosphate-activated protein/protein kinase/liver kinase B1/AMPKα2 (cAMP/PKA/LKB1/ AMPKα2) signaling (Aiyasiding et al, 2022). Liquiritin could decrease the ATE1 protein levels and TAK1 and JNK1/2 phosphorylation induced by angiotensin II (Ang II), which attenuated Ang II-induced cardiomyocyte hypertrophy by regulating the ATE1/TAK1-JNK1/2 pathway (Mo et al, 2022).…”
Section: Cardiac Hypertrophymentioning
confidence: 99%